Jed's corner with Delwin Benson - Johnston, Jedediah (Puppet), interviewer; Benson, Delwin, interviewee; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Jedediah Johnston (puppet) interviews Delwin Benson.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Correction - the first IWRS was in New Mexico, not Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses